'This is your golden time. You enjoy it and you've plenty time for crying after': How dysphagia impacts family caregivers of people with amyotrophic lateral sclerosis – A qualitative study. (September 2020) - Lisiecka, Dominika; Kelly, Helen; Jackson, Jeanne
Background: Dysphagia (swallowing impairments) is a well-recognised symptom of amyotrophic lateral sclerosis. Caring for a person with amyotrophic lateral sclerosis has been recognised as a complex and demanding task. No study to date investigated the impact of dysphagia on the lives of caregivers of people with amyotrophic lateral sclerosis. Aim: To investigate the experiences of dysphagia from the perspective of family caregivers of people diagnosed with amyotrophic lateral sclerosis. Design: Interpretative phenomenological analysis was employed. Individual interviews (n = 15) plus observations of mealtime preparation were conducted, where possible (seven or n). Setting/participants: Participants comprised family caregivers of people with amyotrophic lateral sclerosis and dysphagia living in the South West of Ireland ( n = 10). Findings: Dysphagia transformed the mealtime experiences of the caregivers and changed their approaches to food. Frustration related to the inability to stabilise the weight of the person with amyotrophic lateral sclerosis and the fear of choking emerged strongly. The caregivers strived to ensure the safety of people with amyotrophic lateral sclerosis during meals by providing constant supervision. Despite the challenges precipitated by dysphagia and amyotrophic lateral sclerosis, the caregivers wished to maintain normality for as long as they perceived it to be possible. Conclusion: This study provides a unique contribution in advancing our understanding of the impact of dysphagia on the caregivers of people with amyotrophic lateral sclerosis. Professionals must explore and recognise the needs of the caregivers and provide them with appropriate support, especially how to manage choking.